Changes in gender role attitudes following couples' residential relocations - Sergi Vidal; Philipp M. Lersch (Demographic Research, 2019)
Background: Residential relocations of couple households are associated with increases in objective gender inequality within families in paid and unpaid work. Little is known about how couples' relocations affect subjective outcomes such as attitudes. Objective: We examine whether gender role attitudes change when families move residentially in Britain, empirically addressing potential explanations. We also assess heterogeneity in outcomes by relocation distance and relocation motive. Methods: We use linear fixed-effects regression on a representative sample of 6,415 partnered women and 6,220 partnered men from the British Household Panel Survey (1991–2007). Results: Our results show that, on average, an individual's gender role attitudes were not significantly altered following a couple's relocation. As an exception, we find that when couples exclusively relocated for the female partner's job, men's gender role attitudes became more egalitarian post-relocation. Preliminary evidence also suggests that women's gender role attitudes are potentially affected by their exposure to residential contexts. Contribution: Despite widespread evidence regarding increases in objective gender inequality following couple relocations in Britain, our findings suggest that this does not permeate into subjective outcomes such as attitudes. Beyond expanding the knowledge on subjective sources of gender inequality that follow couples' relocations, our results also contribute to a better understanding of the dynamics of change in gender role attitudes over the life course.
Keywords: 330; attitudes; fixed effects; gender roles; life course; residential mobility; United Kingdom